Mobilization During Critical Illness: A Higher Level of Mobilization Improves Health Status at 6 Months, a Secondary Analysis of a Prospective Cohort Study. Issue 9 (September 2021) - Paton, Michelle; Lane, Rebecca; Paul, Eldho; Cuthburtson, Georgina A.; Hodgson, Carol L.
Abstract : OBJECTIVES: To determine the influence of active mobilization during critical illness on health status in survivors 6 months post ICU admission. DESIGN: Post hoc secondary analysis of a prospective cohort study conducted between November 2013 and March 2015. SETTING: Two tertiary hospital ICU's in Victoria, Australia. PATIENTS: Of 194 eligible patients admitted, mobility data for 186 patients were obtained. Inclusion and exclusion criteria were as per the original trial. INTERVENTIONS: The dosage of mobilization in ICU was measured by: 1) the Intensive Care Mobility Scale where a higher Intensive Care Mobility Scale level was considered a higher intensity of mobilization or 2) the number of active mobilization sessions performed during the ICU stay. The data were extracted from medical records and analyzed against Euro-quality of life-5D-5 Level version answers obtained from phone interviews with survivors 6 months following ICU admission. The primary outcome was change in health status measured by the Euro-quality of life-5D-5 Level utility score, with change in Euro-quality of life-5D-5 Level mobility domain a secondary outcome. MEASUREMENTS AND MAIN RESULTS: Achieving higher levels of mobilization (as per the Intensive Care Mobility Scale) was independently associated with improved outcomes at 6 months (Euro-quality of life-5D-5 Level utility score unstandardized regression coefficient [ β ] 0.022 [95% CI, 0.002–0.042]; p = 0.033; Euro-quality of life-5D-5 Level mobility domain β = 0.127 [CI, 0.049–0.205]; p = 0.001). Increasing the number of active mobilization sessions was not found to independently influence health status. Illness severity, total comorbidities, and admission diagnosis also independently influenced health status. CONCLUSIONS: In critically ill survivors, achieving higher levels of mobilization, but not increasing the number of active mobilization sessions, improved health status 6 months after ICU admission. Abstract : Supplemental Digital Content is available in the text.